Optimization of Short Probe Linear Frequency Modulated Signal Parameters - POGRIBNY, Włodzimierz; LESZCZYŃSKI, Tadeusz (Archives of Acoustics, 2011)
In many physical experiments, linear frequency modulated (LFM) signals are widely used to probe objects in different environments, from outer-space to underwater. These signals allow a significant improvement in measurement resolution, even when the observation distance is great. For example, using LFM probe signals in underwater investigations enables discovery of even small objects covered by bottom sediments.Recognition of LFM (chirp) signals depends on their compression based on matched filtering. This work presents two simple solutions to improve the resolution of the short chirp signals recognition. These methods are effective only if synchronization between the signal and matched filter (MF) is obtained. This work describes both the aforementioned methods and a method of minimizing the effects of the lack of synchronization.The proposed matched filtering method, with the use of $n$ parallel MFs and other techniques, allows only one sample to be obtained in the main lobe and to accurately locate its position in the appropriate sampling period $T_s$ with accuracy $T_{s/n}$. These approaches are appropriate for use in probe signal processing.